2007
DOI: 10.1016/j.jcrs.2006.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Posterior synechias following implantation of a foldable silicone iris-fixated phakic intraocular lens for the correction of myopia

Abstract: A 45-year-old white woman with unilateral high myopia had uneventful implantation of a -9.0 diopter, foldable, iris-fixated Artiflex I anterior chamber phakic intraocular lens (pIOL) (Ophtec B.V.) in the right eye. Despite application of topical antibiotic and steroid agents for 4 weeks after surgery, iris pigment dispersion developed on the anterior surface of the crystalline lens. Two weeks later, the iris dispersion increased and posterior synechias developed from the iris to the crystalline lens next to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…43 The postoperative corneal endothelial cell loss associated with iris-fixated pIOLs via potential mechanical contact between the lens and corneal endothelium should be considered. We found a mean ECC loss of 9.4%.…”
Section: Discussionmentioning
confidence: 99%
“…43 The postoperative corneal endothelial cell loss associated with iris-fixated pIOLs via potential mechanical contact between the lens and corneal endothelium should be considered. We found a mean ECC loss of 9.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical irritation of iris tissue during pupil constriction and dilation may trigger a foreign-body response and lead to breakdown of the blood-aqueous barrier, with subsequent cell adhesions to the IOL. 28,29 Correction of myopic astigmatism with keratorefractive procedures such as femtosecond laser in situ keratomileusis has limitations. Excimer laser treatment can be associated with an increased risk for corneal ectasia and decreased visual quality, especially in eyes with high refractive errors.…”
Section: Discussionmentioning
confidence: 99%
“…However, using the Gullstrand formula, they reported that this effect would induce only a 0.05 diopter (D) refractive change. Other reports of differences in the final positioning of pIOLs in the anterior chamber 7 or the presence of a partially or completely fixed pupil 8 have not demonstrated significant unexpected postoperative refractive results. As in the case by Kohnen et al, 5 we did not find significant (from a theoretical refractive point of view) intraindividual pIOL positioning differences between eyes in any patient.…”
Section: Discussionmentioning
confidence: 84%